النتائج الوظيفية لعلاج كسور جسم عظمي الساعد المغلقة عند البالغين - سعد, معن; المحمد, عزة; رعواني, كنان (Latakia University Journal -Medical Sciences Series, 2019)
يعدّ الساعد ذا بنية تشريحية معقدة تلعب دوراً أساسياً في وظيفة الطرف العلوي , ولقد قدمت كسور الساعد مشاكل فريدة من نوعها في التدبير لعدة سنوات , وإن التحسن الأساسي في تدبير هذه الأذيات كان مقترناً بتطور وسائل التثبيت المستخدمة . يقدم هذا البحث نتيجة المتابعة لكسور جدل الساعد لمدة 3 سنوات في قسم الجراحة في مشفى الأسد الجامعي في الفترة بين الشهر السادس 2007 وحتى الشهر السادس 2010 . شملت الدراسة 36 كسراً في جدل الساعد عند 32 مريضاً , حدث كسر كلا العظمين عند 23 مريضاً (64% ) وكسر الزند لوحده عند 7 مرضى ( 19%) , وكسر الكعبرة وحده عند 6 مرضى ( 17% ) , ولم تصادف أية حالة كسر مختلط بأذية وعائية أو عصبية أو تناذر حجرات . تضمنت طرائق العلاج : العلاج المحافظ والأسياخ داخل النقي والصفائح , تم وضع الجبس بعد الجراحة عند 33 مريضاً ( 92% ) لمدة 4-6 أسابيع وسطياً , تمت متابعة المرضى بشكل دوري سريرياً وشعاعياً . كانت النتائج ممتازة عند 23 مريضاً ( 64% ) وجيدة عند 7 مرضى ( 20% ) ومقبولة عند مريضين (6% ) وسيئة عند 4 مرضى ( 10% ) , تضمنت المضاعفات الاندمال المعيب ( 8% ) وعدم الاندمال (8% ) وعودة الكسر ( 6% ) والأذية العصبية العلاجية ( 8% ) . The forearm is considered the complex anatomic structure that plays very essential role in the function of the upper limb. Fractures of the forearm present a unique management problem for years. Major improvement in the results of management of this injury awaited the development of advanced techniques. Presentation is made of three-year follow up of closed forearm shaft fracture treated at Department of Surgery in the University Al-Assad hospital, in Lattakia. The follow up includes 36 forearm shaft fractures in 32 patients. Complete forearm shaft fractures were recorded in 23 (64%), fractures of the ulna alone in 7 (19%), and of the radius alone in 6 (17%) patients. No compartment syndrome or neuro or vascular injury were encountered. Treatment methods include: conservative treatment, intramedullary nails and plates. Postoperative plaster immobilization was employed in 33 (92%) patients for 4-6 weeks mostly. Patients have been periodically undergone clinical and radiographic assessment. Results were considered excellent in 23(64%), good in 7 (19%), satisfactory in 2 (6%), and poor in 4 (11%) patients. Complications include malunion (8%), nonunion (8%), refracture (6%), and iatrogenic neurologic injury (8%).